2003
DOI: 10.1046/j.1439-0507.2003.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal carriage of Candida species in HIV‐infected patients in India

Abstract: The present investigation represents the first study of oropharyngeal carriage of Candida and other yeasts in HIV-infected patients in India. One hundred and fifty HIV-positive patients were investigated by culturing their swish samples on plates of CHROMagar Candida. Ninety-eight patients (65.3%) were positive for Candida and four (2.7%) were positive for other yeasts. Among them, the first Indian C. dubliniensis isolate has been recovered. Molecular typing of selected C. albicans isolates by AP-PCR revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 34 publications
1
13
0
3
Order By: Relevance
“…Though Candida albicans is the most frequently isolated species as colonizer and pathogen of the oral mucosa, other Candida species, such as Candida tropicalis, Candida krusei , and Candida glabrata are recovered increasingly, mainly in HIV-infected individuals (Gugnani et al, 2003; Hamza et al, 2008; Patil et al, 2015). Candida yeasts cause oropharyngeal, esophageal, laryngeal, and invasive candidiasis (Patil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Though Candida albicans is the most frequently isolated species as colonizer and pathogen of the oral mucosa, other Candida species, such as Candida tropicalis, Candida krusei , and Candida glabrata are recovered increasingly, mainly in HIV-infected individuals (Gugnani et al, 2003; Hamza et al, 2008; Patil et al, 2015). Candida yeasts cause oropharyngeal, esophageal, laryngeal, and invasive candidiasis (Patil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal candidiasis is the most common clinical manifestation in human immunodeficiency virus patients (HIV) (16,24,34). Treatment of this fungal infection presents several problems.…”
Section: Introductionmentioning
confidence: 99%
“…[4910] Present study recorded an overall yeast carriage rate of 48%, which included different Candida species along with other yeasts. This figure is comparable to those reported by Pavithra et al ,[4] from Southern India and Hung et al ,[15] from Taiwan, but lesser than that of a similar study carried out a decade ago by Gugnani et al [10] (68% - included 65.35% Candida and 2.7% other yeasts) from New Delhi. A recent study by Maurya et al ,[5] reported a carriage rate of 33.1% in a similar group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[78] In the Indian scenario, only a few reports are available on asymptomatic carriage of yeasts in the oral cavity of HIV seropositive individuals. [345910] Most of these studies are, however, from the southern states of the country. [349] Of these, still fewer studies have looked for the association of yeast carriage in relation to CD4 + count.…”
Section: Introductionmentioning
confidence: 99%